A reduced-order crystal model for HCP metals: Application to Mg. (July 2016) - Becker, R.; Lloyd, J.T.
Highlights: A reduced order crystal plasticity model for HCP crystals is proposed to ease computational requirements. The model includes twinning, basal slip and a rate dependent isotropic component representing combined pyramidal and prismatic slip. The model successfully reproduces tension compression asymmetry and saturation from twinning and basal slip at only approximately five times the cost of a J2 flow theory model. Abstract: A computationally efficient plasticity model for HCP crystals is developed for use in simulations where the constitutive model evaluations account for a significant fraction of the total analysis time. Combined pyramidal and prismatic slip is represented as an isotropic function while slip along the basal plane and extension twinning are maintained as distinct mechanisms. Additional efficiency is gained by deferring the updates of the rate-independent twinning and basal system strengths until the following time step, which allows precomputation of the inverses of the slip interaction matrices. Comparisons are made with single crystal pure Mg experimental data, as well as rolled polycrystal AZ31B data. The computational efficiency is evaluated by comparing simulation times from the current model with J2-Flow theory plasticity and a full crystal plasticity model. The reduced crystal plasticity model retains essential crystallographic features that govern macroscale mechanical response of HCP metals at approximately five times the computational expense of a J2-Flow theory calculation.